2008
DOI: 10.1016/j.jcrs.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Optical quality of the eye after lens replacement with a pseudoaccommodating intraocular lens

Abstract: Implantation of the pseudoaccommodating IOL in healthy eyes yielded uncorrected levels of high-contrast, distance, and near acuities comparable to preoperative best corrected values. Higher-order aberration levels appeared to be similar to the preoperative values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
2
39
1
1
Order By: Relevance
“…Multifocal patients reported less limitation in visual function and less spectacle dependency than patients with Mean, high-contrast, binocular visual acuity (logMAR) with a best correction for distance vision, as a function of the chart vergence for the AcrySof ReSTOR aspheric IOL (SN6AD3 model). Red circular symbols show data from the present study, black symbols are data from Blaylock et al 18 (SN60D3 model), blue symbols from Alfonso et al 12 (SN60D3 model) and green symbols from Montés-Micó et al 19 (SN60D3 model). Data from Baylock et al 18 , Alfonso et al 12 , and for the present study were obtained by varying the chart distance and from Montés-Micó et al 19 by altering chart vergence with lenses (last one was corrected for lens effectivity and spectacle magnification at the 15 mm vertex distance used).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Multifocal patients reported less limitation in visual function and less spectacle dependency than patients with Mean, high-contrast, binocular visual acuity (logMAR) with a best correction for distance vision, as a function of the chart vergence for the AcrySof ReSTOR aspheric IOL (SN6AD3 model). Red circular symbols show data from the present study, black symbols are data from Blaylock et al 18 (SN60D3 model), blue symbols from Alfonso et al 12 (SN60D3 model) and green symbols from Montés-Micó et al 19 (SN60D3 model). Data from Baylock et al 18 , Alfonso et al 12 , and for the present study were obtained by varying the chart distance and from Montés-Micó et al 19 by altering chart vergence with lenses (last one was corrected for lens effectivity and spectacle magnification at the 15 mm vertex distance used).…”
Section: Discussionmentioning
confidence: 73%
“…Red circular symbols show data from the present study, black symbols are data from Blaylock et al 18 (SN60D3 model), blue symbols from Alfonso et al 12 (SN60D3 model) and green symbols from Montés-Micó et al 19 (SN60D3 model). Data from Baylock et al 18 , Alfonso et al 12 , and for the present study were obtained by varying the chart distance and from Montés-Micó et al 19 by altering chart vergence with lenses (last one was corrected for lens effectivity and spectacle magnification at the 15 mm vertex distance used). Note that some points on the graph at the same vergence were slightly displaced to facilitate visualization.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Researchers have recently demonstrated that certain combinations of nonrotationally symmetric aberrations, such as coma and astigmatism, can result in better retinal image quality as compared to the condition with the same amount of astigmatism alone (de Gracia et al, 2010). Other authors have studied the effect of cataract surgery on the optical aberrations of the eye, and astigmatism in particular (Montés-Micó et al, 2008;Guirao et al 2004;Marcos et al, 2007). Most of these studies found that astigmatism increased significantly after surgery.…”
Section: Clinical Assessment Of Retinal Image Quality In Eyes With Asmentioning
confidence: 99%